A long journey coming to fruition: In sight of the pre-selection T-cell repertoire - Ciucci, Thomas (Eur J Immunol, 2016)
In addition to MHC restriction and its structural correlate, the recognition of an MHC-peptide complex by the T-cell antigen receptor (TCR), T-cell reactivity is constrained by positive and negative selection in the thymus. While mouse genetic studies have provided compelling evidence for both processes, the actual impact of selection on the mature T-cell repertoire has remained difficult to assess, in particular because it has so far not been possible to follow the intrathymic differentiation of antigen-specific T cells carrying endogenous TCR specificities. In this issue of the European Journal of Immunology, Hesnard et al. [Eur. J. Immunol. 2016. 46: XXXX-XXXX] report the detection of human antigen-specific immature thymocytes, thereby opening the way to addressing these questions. Here we discuss the implications of this technological advance.